Adenoid Cystic Carcinoma from the salivary and lacrimal glands and the breast: Different clinical outcomes to the same tumor. (November 2022) - Emerick, Carolina; Mariano, Fernanda Viviane; Vargas, Pablo Agustin; Nör, Jacques E.; Squarize, Cristiane H.; Castilho, Rogerio M.
Abstract: Adenoid cystic carcinoma (ACC) is a biphasic malignant lesion that can develop at various anatomical sites. Salivary and lacrimal ACC lesions have a high risk of local invasion, metastasis, and poor prognosis. In more distant organs, such as the breast, ACC is a rarer and less aggressive lesion. One of the major predictors of mortality of ACC is perineural invasion, which can be seen in 30 % of breast lesions, 85% of salivary lesions, and almost 100 % of lacrimal gland tumors. The biological differences between these three ACC tumors are still poorly understood. We focused on the current understanding of the genetic variations observed on ACC tumors and prognostic differences associated with distinct anatomical sites. A special effort was made to present the currently available therapies alongside the emerging strategies under development. Graphical Abstract: ga1 Highlights: The most common anatomical site for Adenoid Cystic Carcinoma is the salivary gland. Lesions in the lacrimal gland and breast can also be found, but are much rarer. Perineural invasion is a problem that mainly affects salivary and lacrimal lesions. Breast lesions have a better prognosis among the three anatomical sites. Clinical trials and cell lines studies are based on salivary gland lesions.